2023
DOI: 10.3389/fpls.2022.1043757
|View full text |Cite
|
Sign up to set email alerts
|

Combined metabolomic and transcriptomic analysis reveals key components of OsCIPK17 overexpression improves drought tolerance in rice

Abstract: Oryza Sativa is one of the most important food crops in China, which is easily affected by drought during its growth and development. As a member of the calcium signaling pathway, CBL-interacting protein kinase (CIPK) plays an important role in plant growth and development as well as environmental stress. However, there is no report on the function and mechanism of OsCIPK17 in rice drought resistance. We combined transcriptional and metabonomic analysis to clarify the specific mechanism of OsCIPK17 in response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 92 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…Consequently, it is hypothesized that CIPKs may influence the production of citric acid by modulating intracellular Ca 2+ levels in plants. The OsCIPK17 gene in rice has been demonstrated to enhance rice drought resistance and play a role in the citric acid accumulation within the citrate cycle [ 80 ]. Ca 2+ have the potential to enhance soybean tolerance to aluminum ions (Al 3+ ) by stimulating citric acid secretion and mitigating oxidative stress damage [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it is hypothesized that CIPKs may influence the production of citric acid by modulating intracellular Ca 2+ levels in plants. The OsCIPK17 gene in rice has been demonstrated to enhance rice drought resistance and play a role in the citric acid accumulation within the citrate cycle [ 80 ]. Ca 2+ have the potential to enhance soybean tolerance to aluminum ions (Al 3+ ) by stimulating citric acid secretion and mitigating oxidative stress damage [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, genes and metabolites related to sugar metabolism were less changed in ‘Pacific Early’, indicating that ‘Pacific Early’ failed to produce more osmoregulatory substances to resist drought stress. The TCA cycle is an important component of plant energy metabolism [ 21 , 23 , 47 ]. In this study, in ‘Jilv3’ under drought stress, the TCA cycle was enhanced by the upregulation of related DEGs, including SDH , CS , SDH , and IDH , which could efficiently improve the utilization of malic acid, citric acid, and succinic acid.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the transcriptome and metabolome of Cyclocarya paliurus under different PEG concentrations were analyzed, and WGCNA revealed that 3 key modules, 8 structural genes and 14 regulatory transcription factors regulate sugar metabolism under drought stress (Li et al, 2023a). By combining transcriptomics and metabolomics, researchers showed that OsCIPK17 positively regulates drought resistance in rice and is involved in the accumulation of citrate in the TCA cycle (Lu et al, 2023). Transcriptome and metabolome analyses of Illicium difengpi under drought stress and water replenishment revealed that there were more genes with upregulated expression than genes with downregulated expression, and water replenishment treatment induced the stable expression of 65.25% of genes (Zhang et al, 2024).…”
Section: Introductionmentioning
confidence: 99%